Digital narratives and the legitimation of narcotourism: a critical perspective from Latin American thanatourism - Guerrero-Sierra, Hugo; Wilches Tinjacá, Jaime Andrés; Franco Correa, Andrea (Frontiers in Political Science, 2025)
Dark tourism (or thanatourism) has emerged as one of the most dynamic and controversial segments of the global tourism industry. In Latin America, particularly in Colombia, Bolivia, and Mexico, this phenomenon intersects with the legacy of drug trafficking, producing a form of tourism that blends fascination with violence, symbolic consumption, and digital mediation. This article aims to identify the narratives that sustain the appeal of narco-tourism and to analyze how these narratives are constructed, circulated, and legitimized through digital platforms. The study adopts a qualitative methodological approach, combining multimodal discourse analysis with digital ethnography, and focuses on user-generated content from tourism platforms and social media. The findings reveal the emergence of prototypical narratives that aestheticize drug lords as transgressive heroes, while omitting the structural violence and illegality underpinning their histories. These narratives are not only reproduced by tourists but also amplified by tourism operators and tolerated by state institutions, contributing to the normalization of narco-culture as a legitimate form of cultural consumption. The article concludes by reflecting on the ethical and political implications of this trend, and calls for a critical rethinking of tourism practices in contexts marked by violence and historical trauma.